ГЛОБАЛІЗАЦІЯ ТА УКРАЇНСЬКІ КУЛЬТУРНІ ІДЕНТИЧНОСТІ: ПОЛІЦЕНТРИЗМ, ТОТАЛЬНІСТЬ, ХОЛІСТИЧНІСТЬ - ТИТАР, О. В. (Вісник Харківського національного університету імені В. Н. Каразіна. Серія «Теорія культури і філософія науки», 2015)
У нашій роботі досліджені українські культурні ідентичності в умовах глобалізації,визначені сумісні характеристики тотальних, холістичних та полікультурнихідентичностей. Поняття тотальної та холі стичної ідентичності говорить про різнірівні цілісності та фрагментованості сучасної глобалізованої ідентичності. Холі стичнаідентичність характеризується єдністю аксіологічних та естетичних параметрів,розчиненню ідеальних конструктів у повсякденному, тотальна характеризуєтьсяпротиріччями між ідеалом та його втіленням, цінностями та їхнім втіленням. Тобто вглобалізованих ідентичностях ми можемо говорити про різні рівні синтезу такомунікативних практик.Титарь Е. В. ГЛОБАЛИЗАЦИЯ И УКРАИНСКИЕ КУЛЬТУРНЫЕ ИДЕНТИЧНОСТИ:ПОЛИЦЕНТРИЗМ, ТОТАЛЬНОСТЬ, ХОЛИСТИЧНОСТЬ В нашей работе исследованыукраинские культурные идентичности в условиях глобализации, определены сущностныехарактеристики тотальных, холистических и поликультурных идентичностей. Понятиятотальной и холистической идентичности говорят о разных уровнях целостности ифрагментирования современной глобализированной идентичности. Холистическаяидентичность характеризуется единством аксиологических и эстетическихпараметров, растворением идеальных конструктов в мире повседневного. Тотальнаяидентичность характеризируется противоречиями между идеалом и его воплощением,ценностями и их воплощением. Таким образом в глобализированных идентичностях мыможем говорить о разных уровнях культурного синтеза и разных коммуникативныхпрактиках.Ключевые слова: идентичность, коммуникация, тотальность, холизм,поликультурность, глобализация, тотальная культурная идентичность, холистическаякультурная идентичность.Tytar Olena GLOBALIZATION AND UKRAINIAN CULTURAL IDENTITY:POLYCENTRICITY, TOTALITY, HOLISTICS Space and time in the functioning of identity arenot just a postmodern "space - time compression," or a specific sequence of events and "places",space and time are filled with events that got the valued differentiation. Based on theseaxiological characteristics the acceleration of time and centring operate near the determined keylocations of space. Appear fuller and less filled with social meaning social plane, space, socialattention and social neglect, resulting in information and social streams, creating new forms ofcentering. For example, the concept of Hannah Arendt draws attention to the fact that the stateloses the capacity for such alignment, creating an "empty political space" that is deprived formerinfluence on forming and functioning of cultural identitiesThe concept of "individualized society" Z. Bauman is based on the consideration of culturalidentities as a postmodern individualized, they survived the dismantling of the collective is theinstitutionalized framework of finding individuality. But, in our view, is not only dismantling ofsocial institutions, including the state, but also the formation of new social institutions, moreflexible than the old. Such institutions can be called (M. Castells terms) social and informationflows, which are not less inclusive than the old institutions. In addition, our study has receivedconsiderable attention to the fact that for a holistic identity is not specific blurring concept of thecenter, and the existence of many centers - polycentricity. Here we use the metaphor of thenetwork society in which there are a lot of sites and centers of gravity, and the decline in thevalue of one of the centers of communication in general, leads to a decline in the integral part ofsuch a communication network.In our work Ukrainian cultural identity in the conditions of globalization is analyzed, definedthe essential characteristics of a total, holistic and multicultural identities. The concept of totaland holistic identity talk about different levels of integrity and fragmentation of modernglobalized identity, about the different types of compounds of these identities with internal andexternal communication, the different levels of its functioning in social integration. Holisticidentity is based on simultaneously, which provides the current level of technology andcommunications, and cyclically of the information society, correlate with the natural cycles.Total identity is based on the fragmentation and merging fragments of space-time in a specificsequence, which depends on the alignment of social (social needs, the rate of social processes).Total identity replaces the cyclic compound ephemeral time (instantaneous) and the eternal.Holistic identity characterized by unity axiological and esthetic parameters, dissolution idealconstructs in the everyday world. Total identity is characterized by contradictions between theideal and its embodiment, values and their realization. Thus, in the globalized identities we cantalk about different levels of cultural synthesis and different communicative practices.Key words: identity, communication, totality, holism, multiculturalism, globalization, totalcultural identityl, holistic cultural identity.